Relacje małżeńskie Jadwigi Andegaweńskiej i Władysława Jagiełły w Rocznikach Jana Długosza .......... 87 - Cira, Natalia (Od Sumeru do zimnej wojny, 2025)
MARRIAGE RELATIONS OF JADWIGA OF ANJOU AND WŁADYSŁAW JAGIEŁŁO IN JAN DŁUGOSZ’S ANNALESThe aim of this article is to present how Jan Długosz depicted the marriage of Jadwiga of Anjou and Władysław Jagiełło in his Annals. The author focuses mainly on their private relationship, omitting political matters. The goal was to answer the questions: to what extent does Długosz’s portrayal of the marital relationship reflect reality, and what influenced his opinion on the matter? The primary sources for this work are books X and XI of the Annals. The author traces the couple’s relationship from the beginning of their marriage until Jadwiga’s death. According to Długosz, the queen was initially fearful of marrying a pagan. The author believes that this claim may be accurate. She also addresses the motivations that, according to the chronicler, led the Lithuanian duke to marry Jadwiga, with her beauty being a leading factor. An important issue affecting the relationship between the two spouses was Jadwiga’s connections with Wilhelm Habsburg. The author firmly rejects the theory that the queen loved him and questions the authenticity of Długosz’s account of the couple’s meetings after Jadwiga’s marriage to Jagiełło. She also considers Długosz’s account of the trial of Gniewosz of Dalewice to be inaccurate. However, she does not rule out that the chronicler was correct regarding the later happy marital life of Jadwiga and Jagiełło. The author also examines the accuracy of Długosz’s claim about Władysław’s absence during his wife’s death and the role Jadwiga played in the king’s life. Długosz particularly emphasized Jadwiga’s exceptional status among Jagiełło’s other wives. The significance of her influence on the monarch is evidenced by Długosz’s account of Władysław, on his deathbed, giving her engagement ring to Zbigniew Oleśnicki. The author agrees with Długosz regarding the exceptional character of Jadwiga and the influence she may have had on Jagiełło. In the article, the author demonstrates that the chronicler’s account of the marital relationship is invaluable. Unfortunately, Jan Długosz often strayed from the truth, but his Annals remain the only source that allows even a partial reconstruction of the marriage between Jadwiga of Anjou and Władysław Jagiełło.